Analisis Persaingan Perbankan Syariah Indonesia: Aplikasi Model Panzar-Rosse - Kasri, Rahmatina A.; lman, Nur (UI Scholars Hub, 2010)
Indonesia is among the few countries that adopts dual banking system where Islamic banks run in parallel and compete with conventional banks. Although under such a system banking competition would be expected to be high, data tend to show the opposite case, as three Islamic banks acquired 65 percent of market share in Indonesia. This study, therefore, attempts to determine the degree of banking competition in Indonesia by employing the Panzar-Rosse Model for 2003-2008 period. The study also analyses the competitive behaviors of Islamic banks and compares it with those of its conventional connterparts. The estimated model suggests that monopolistic competition exists in the overall banking industry-the degree is even slightly higher for Islamic banking, where the market is characterized by aggressive competition for funding, quality human resources, and financing. Such competition occurs due to, among others, small market size, low consumer base, lack of product variations, and la.ck of competent human resources. These should be a major concern for all Islamic banking stakeholders for developing a better Islamic banking industry, particularly in Indonesia.